Improved Healing after the Co-Transplantation of HO-1 and BDNF Overexpressed Mesenchymal Stem Cells in the Subacute Spinal Cord Injury of Dogs - Khan, Imdad Ullah (Cell Transplant, 2018)
Abundant expression of proinflammatory cytokines after a spinal cord injury (SCI) creates an inhibitory microenvironment for neuroregeneration. The mesenchymal stem cells help to mitigate the inflammation and improve neural growth and survival. For this purpose, we potentiated the function of adipose-derived mesenchymal stem cells (Ad-MSCs) by transfecting them with brain-derived neurotrophic factor (BDNF) and heme oxygenase-1 (HO-1), through a lentivirus, to produce BDNF overexpressed Ad-MSCs (BDNF-MSCs), and HO-1 overexpressed Ad-MSCs (HO-1-MSCs). Sixteen SCI beagle dogs were randomly assigned into four treatment groups. We injected both HO-1 and BDNF-overexpressed MSCs as a combination group, to selectively control inflammation and induce neuroregeneration in SCI dogs, and compared this with BDNF-MSCs, HO-1-MSCs, and GFP-MSCs injected dogs. The groups were compared in terms of improvement in canine Basso, Beattie, and Bresnahan (cBBB) score during 8 weeks of experimentation. After 8 weeks, spinal cords were harvested and subjected to western blot analysis, immunofluorescent staining, and hematoxylin and eosin (H&E) staining. The combination group showed a significant improvement in hindlimb functions, with a higher BBB score, and a robust increase in neuroregeneration, depicted by a higher expression of Tuj-1, NF-M, and GAP-43 due to a decreased expression of the inflammatory markers interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α), and an increased expression of interleukin-10 (IL-10) (P ≤ 0.05). H&E staining showed more reduced intraparenchymal fibrosis in the combination group than in other groups (P ≤ 0.05). It was thus suggested that the cotransplantation of HO-1 and BDNF-MSCs is more effective in promoting the healing of SCI. HO-1-MSCs reduce inflammation, which favors BDNF-induced neuroregeneration in SCI of dogs.